Legal politics countermeasures of prostitutions criminalization policy perspective in Indonesia - Martha, I Dewa Agung Gede Mahardika; Setiabudhi, I Ketut Rai; Setyorini , Erny Herlin (Technium Social Sciences Journal, 2022)
Prostitutions is one of the eldest phenomenon, ones that occurs in Indonesia, Penal Law in Indonesia did not regulate the prostitution activities in case of these 3 (three) components; the pimps or brothel keepers and sex workers or the prostitutes. In this research these are the problems that occurs: 1.) why prostitutions are classified as social problems in the community? 2.) How is the legal politics to countermeasures prostitutions from Policy Perspective? This research was conducted with Normative method. Prostitutions is classified as social problems in the community it is because of the negative consequences impacted by the prostitutions. Social consequences from prostitutions are crimes and narcotics, whereas both of them are correlated with prostitutions, from the medical perspectives are also impacted, such as HIV-AIDS. Legal politics of Prostitutions Countermeasures is to Criminalize the prostitutes and their consumers, this can be asked to the legislatives of legislator who choose and decides the options to countermeasures this phenomenon from every alternatives that available in the process of the legal formulating that corresponding with the constitutions and Pancasila as the base of Indonesia Legal System.